Twitter based Analytics for Business Footprints of the Banking Sector in India - Ambulkar, Sheetal; Saraf, Akshay; Chitre, Neeranjan (International Journal of Engineering and Technology, 2018)
Twitter is one of the worldâ€™s most popular social media platforms with over 330 million users. Many businesses use Twitter to reach and connect with their customers. There are a number of advantages that using twitter can bring to a business. Some of the prominent advantages of tweeter platform to the businesses are the reach to broad spectrum of customers worldwide, delivery of customer services, establishment of brand identity, gathering customer feedback etc. The best part of it is that these advantages are at the free of cost. This paper proposes a system, that can help the banking sector in India, to compare their impression on the general customer by analyzing the tweets by the banking organizations and the replies by their customers The analysis includes the tweet handles by two nationalized banks (State Bank of India and Punjab National Bank) and two private sector banks (ICICI and HDFC).Â Â